Animals in the COVID-19 Era: Between Being a source, Victims, or Maybe our Hope to Overcome it! - Shilpi Gupta; Hoda Elkhenany; Prabhat Kumar; Faten A. Okda (International Journal of Coronaviruses, 2020)
The indirect misuse of animals usually correlated to catastrophic consequences like the one we are facing now, novel coronavirus disease-19. However, the source of infection is not fully confirmed yet. But the finger of blame points to bats and pangolins. Hence, understanding and raising awareness about wild animals and the consequences of their misuse are a must to avoid future pandemics. Herein, we threw light on the most animals involved in the current epidemic as well as possible animals in the shadow. Random serological investigations of samples from animals of different species (including asymptomatic animals) are required to understand the prevalence and severity of the infection, the extent of the transmission, and the monitoring of the situation over time. Moreover, alleviating fear associated with the possibility of human infection from their pets, we highlight that there are no reports that confirm this hypothesis; however, the opposite has been reported. Similarly, there is no proof that pigs can become infected amplify or spread novel coronavirus.
Keywords: COVID-19